CD74 knockout protects against LPS‐induced myocardial contractile dysfunction through AMPK‐Skp2‐SUV39H1‐mediated demethylation of BCLB. (11th February 2020) - Luo, Yuanfei; Fan, Congcong; Yang, Mingjie; Dong, Maolong; Bucala, Richard; Pei, Zhaohui; Zhang, Yingmei; Ren, Jun
Abstract : Background and Purpose: Lipopolysaccharides (LPS), an outer membrane component of Gram‐negative bacteria, triggers myocardial anomalies in sepsis. Recent findings indicated a role for inflammatory cytokine MIF and its receptor, CD74, in septic organ injury, although little is known of the role of MIF‐CD74 in septic cardiomyopathy. Experimental Approach: This study evaluated the impact of CD74 ablation on endotoxaemia‐induced cardiac anomalies. Echocardiographic, cardiomyocyte contractile and intracellular Ca 2+ properties were examined. Key Results: Our data revealed compromised cardiac function (lower fractional shortening, enlarged LV end systolic diameter, decreased peak shortening, maximal velocity of shortening/relengthening, prolonged duration of relengthening and intracellular Ca 2+ mishandling) and ultrastructural derangement associated with inflammation, O2 − production, apoptosis, excess autophagy, phosphorylation of AMPK and JNK and dampened mTOR phosphorylation. These effects were attenuated or mitigated by CD74 knockout. LPS challenge also down‐regulated Skp2, an F‐box component of Skp1/Cullin/F‐box protein‐type ubiquitin ligase, while up‐regulating that of SUV39H1 and H3K9 methylation of the Bcl2 protein BCLB. These effects were reversed by CD74 ablation. In vitro study revealed that LPS facilitated GFP‐LC3B formation and cardiomyocyte defects. These effects were prevented by CD74 ablation. Interestingly, the AMPK activator AICAR, the autophagy inducer rapamycin and the demethylation inhibitor difenoconazole inhibited the effects of CD74 ablation against LPS‐induced cardiac dysfunction, while the SUV39H1 inhibitor chaetocin or methylation inhibitor 5‐AzaC ameliorated LPS‐induced GFP‐LC3B formation and cardiomyocyte contractile dysfunction. Conclusion and Implications: Our data suggested that CD74 ablation protected against LPS‐induced cardiac anomalies, O2 − production, inflammation and apoptosis through suppression of autophagy in a Skp2‐SUV39H1‐mediated mechanism.